A new proposal to improve the customer competitive benchmarking in QFD. Issue Volume 30:Issues 4(2018) (2nd October 2018) - Franceschini, Fiorenzo; Maisano, Domenico
ABSTRACT: Quality Function Deployment (QFD) is a structured tool that supports the design of new products/services, translating customer requirements into technical and process characteristics. The so-called Customer Competitive Benchmarking is a module of the QFD's House of Quality, in which a sample of (potential) customers express their perceptions on a set of competing products/services; this information is then elaborated by a cross-functional team of experts and used to define improvement and strategic goals. Despite the importance of this kind of benchmarking for the whole QFD process, the scientific literature reveals limited research. This article critically analyzes the traditional procedure of customer-competitive benchmarking, highlighting its major weaknesses and problematic aspects. Additionally, it proposes an alternative procedure to overcome (at least partly) those weaknesses, without undermining the simplicity in data collection and processing of the traditional procedure. The alternative procedure utilizes the Thurstone's Law of Comparative Judgment, which allows to transform subjective judgments by multiple respondents into a collective cardinal scaling. The description is supported by several pedagogical and real-life examples.